Correlation between minimum apparent diffusion coefficient values and the histological grade of breast invasive ductal carcinoma - Zhao, Suhong (Oncol Lett, 2018)
The present study aimed to investigate the correlation between the minimum apparent diffusion coefficient (ADC(min)) value and the histological grade of breast invasive ductal carcinoma (IDC). In total, 129 pathologically verified lesions that were subjected to dynamic breast magnetic resonance imaging and diffusion weighted imaging prior to biopsy were included. The ADC(min) value was calculated and its correlation with the tumor histological grade was investigated. Tumors of lower grades demonstrated significantly higher ADC(min) values as compared with tumors of higher grades (F=33.49; P<0.01). The mean ADC(min) values for IDC of grades I, II and III were (1.14±0.11)×10(−3), (0.99±0.12)×10(−3) and (0.86±0.13)×10(−3) mm(2)/sec, respectively. Statistically significant differences were detected in the mean ADC(min) value between tumors of grades II and III (P<0.01), as well as between tumors of grades I and II (P<0.01). In addition, the mean ADC(min) values for the less aggressive (grades I and II) and more aggressive (grade III) groups were (1.01±0.13)×10(−3) and (0.86±0.13)×10(−3) mm(2)/sec, respectively (t=5.76, P<0.01). In conclusion, these data indicated that the ADC(min) value was correlated with the IDC histological grade, and lower ADC(min) values were associated with a higher histological grade and more aggressiveness. Thus, the ADC(min) value may be considered as a promising prognostic parameter in identifying tumor aggressiveness.